Detailed comfort analysis of the cooling system in the 16th century Villa Aeolia (Costozza, Italy). Issue 3 (September 2019) - Ferrucci, Margherita; Peron, Fabio
Abstract: The villas of Costozza (Vicenza, Italy), built in 16th century, give an example of bioclimatic architecture actual even today. These villas are connected to a large underground cavities network present inside the nearby hills, that can dissipate heat to the ground and provide cool air in summer. Here is analysed Villa Aeolia, still in operation, modelling its natural cooling system in a day of July by using steady-state 3D Fluid Dynamics computations. We focus on three scenarios depending on the outdoor temperature, that follows the daily temperature variations. The simulations let us to know the indoor velocity field and the temperature distribution in the main hall, the Sala Apollinea. Then, we evaluate the global thermal comfort and local discomfort by determining the sensation index Predicted Mean Vote, Predicted Percentage of Dissatisfied and Draught Rating at 1.1 m above the hall floor. This method can easily be implemented in others cases and allows to have a spatial evaluation of comfort and therefore to identify in the different scenarios which are the parameters on which to act in the event of local discomfort.